Study on the protective effect and mechanism of paeonol on myocarditis in sepsis mice - LIU Yun, ZHANG Xiaobing, ZHANG Xiangming, XIA Siliang (Zhongguo linchuang yanjiu)
Objective To investigate the protective and anti-inflammatory effects of paeonol (PAE) on lipopolysaccharide (LPS) -induced myocarditis in septic mice. Methods A total of 30 male C57/bl-6 mice were randomly divided into 5 groups, with 6 mice in each group: control group, model group (LPS), and low, medium and high dose treatment groups (LPS+PAE). The control group was intraperitoneally injected with 1 mL/kg normal saline, and the other 4 groups were intraperitoneally injected with 10 mg/kg LPS to establish sepsis mouse models. After that, the control group and the model group were intragastrically administered with normal saline 10 mL/kg every day, while the treatment groups were intragastrically administered with PAE 25, 50 and 100 mg/kg for 3 consecutive days, respectively. The protein expression levels of p-P65, BAX, TNF-α and mTOR in myocardial tissue were detected. Hematoxylin-eosin (HE) staining was used to observe myocardial fiber swelling, inflammatory cell infiltration and apoptosis. Cardiomyocytes H9C2 were cultured and induced by LPS of 1 μg/mL to establish an inflammatory response model. The cardiomyocytes were treated with PAE of 25, 50, 100 μmol/L. p-P65 expression was detected by immunofluorescence. Results Compared with normal group, TNF-α, BAX, p-P65 and mTOR were increased in model group (P＜0.05). In paeonol treatment groups, TNF-α, BAX, p-P65 and mTOR decreased (P＜0.05). The protein expression levels of p-P65, BAX, TNF-α and mTOR could be significantly decreased in high-dose treatment group (P＜0.05). The myocardium of the model group had more collagen fibers and disordered myocardium structure. Compared with the model group, the high dose paeonol treatment group made the myocardial tissue structure closer to normal. Conclusion Paeonol can protect myocardium and reduce inflammatory damage, and its mechanism may be related to the anti-apoptotic ability of mTOR.